Complexities of the Relationship between Shades of Meaning and Polysemy in English and Arabic in the context of Translation: A Case Study of Translation Samples from Online Reverso Dictionary from the Website 'www. context.Reverso.net' - Manal Eltayeb Mohamed Idris (International Journal of Linguistics, Literature and Translation, 2025)
This study explores the complex relationships between two important concepts: Shades of meaning and polysemy within the context of translation studies. This study also in fact a case study uses Reverso AI-based translation tool to examine the role of Artificial Intelligence (AI) in finding more accurate equivalents and widening learners' abilities in understanding contextual and textual meanings,  and the wide and subtle differences of equivalent word, and how meaning could varies in this interactive relation between the English and Arabic languages. This study will delve into wide examples and analysis of the nuances of meaning (shades of meaning) and the phenomenon of polysemy (multiple meanings of a word) in both English and Arabic. Using Reverso Application as a case study, the study leveraged the Application as a sensitive language tool to examine these complications of accurate Arabic equivalent. Reverso is a French Application based on neural machine translation (NMT). Reverso provides translation, synonyms, conjugations and context sentences, and It’s also a useful way to find multi-word translations, colloquial expressions and slang terms that won’t normally translate accurately in a standard dictionary or translation tool like Google Translate. The findings stress the advantages of using this application, while at stress on the human translators to adjust such translations, and stress the importance of accurate equivalent considering shades of meaning and the various equivalents of Polysemous. This research paper contributes significantly to translation studies that focuses on new technology of Artificial intelligence (AI), and the promising results that would be gained by using this Application in English-Arabic translation.